SKILLS HOW TO IMPROVE LISTENING COMPREHENSION SKILLS - Omonova Muxlisa O'zbekiston davlat jahon tillari universiteti Roman-german filologiyasi fakulteti 1-bosqich talabasi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Listening comprehension is a fundamental skill in language learning that enables effective communication and understanding of spoken language. This article explores common challenges learners face when developing listening skills and provides practical methods and strategies to improve listening comprehension. It emphasizes the importance of active listening, creating a conducive environment, and maintaining motivation and consistency in practice. Keywords Listening comprehension, language learning, active listening, listening skills improvement, listening practice, concentration, motivation